The right to property from the perspective of fundamental rights: challenges from the perspective of comparative jurisprudence - Rodríguez Moscoso, Jimena Zoila (2023)
This paper has the object to identify the content of the right to property from doctrinal and jurisprudence perspective, which assess the obligations arising from this right for its effective implementation, as well as identify actions for its effective implementation.